Case Report: Integrated echocardiographic assessment guided Liwen procedure for treating obstructive hypertrophic cardiomyopathy with ventricular aneurysm - Zhang, Rui; Zhao, Fan; Wang, Jing; Qin, Yahong; Wang, Tingting; Chu, Ai-Ai (Frontiers in Cardiovascular Medicine, 2023)
Hypertrophic cardiomyopathy (HCM) is a genetic myocardial disease, with an estimated incidence of 0.2%–6%, and is the main cause of sudden cardiac death (SCD) in young athletes. Left ventricular apical aneurysm (LVAA) is a rare subtype of HCM, accounting for about 5% of HCM patients, and has a higher incidence of cardiovascular adverse events. In cases of hypertrophic obstructive cardiomyopathy with LVAA (HOCM-LVAA) that do not respond adequately to optimized medical therapy, the echocardiography-guided percutaneous intra-myocardial septal radiofrequency ablation (PIMSRA, Liwen procedure) emerges as a promising and effective novel therapeutic approach. In this case report, we present for the first time a comprehensive application of echocardiographic techniques, including TTE, 2-D STE, and contrast enhancement, in the diagnosis, treatment, surgical guidance, and assessment of therapeutic outcomes in a case of HOCM-LVAA.